Pengukuran Daerah Genangan di Pesisir Bangkalan Akibat Naiknya Muka Air Laut [Pridiction Of Inundation Area At Bangkalan Coastal Region Resulted In Sea Level Rise] - Achmad Fachruddin Syah (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Climate change and anticipates impacts of sea level rise such as increased coastal erosion, inundation, and salt water intrusion will affect all countries but mostly small island countries of oceans and low lying lands along coastlines. Indonesia as an archipelago country will also received this impact. Thus, a coastal vulnerability assessment of Indonesia to sea level rise is needed as a part of coastal zone management. Bangkalan one of Indonesia's coastal regions has been dealing with coastal erosion and its vulnerability will more by sea level rise. Prediction to inundation at Bangkalan coastal region for next 20 and 50 years show that area of inundation will increase especially at several subdistricts such Kamal, Socah, Bangkalan dan Klampis